Pengaruh Pelatihan, Kemampuan Kerja Dan Lingkungan Kerja Terhadap Kinerja Tenaga Kerja Indonesia (Studi Pada Dinas Tenaga Kerja, Tranmigrasi Dan Sosial Kota Semarang) - Millan, Alston; Pratiwi, Eka; Sirante, Yohanis (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract:The purpose of this study was to determine the effect of training, work ability and work environment on the performance of Indonesian workers abroad. In this study data was collected by means of observations, interviews and questionnaires on 50 respondents. The analysis used includes test data instruments (validity test, and reliability test), multiple linear regression analysis, classic assumption test (normality test, multicollinearity test, heteroscedasticity test), and hypothesis testing (f test, t test, coefficient of determination). From the results of the analysis using regression, it can be seen that training variables, work ability and work environment, all have a positive effect on the performance of Indonesian workers. From the t-test results obtained from training, work ability and work environment, all have a significant effect on the performance of Indonesian workers.Keywords: Training, Work Ability, Work Environment And Workforce Performance Indonesia